2019
DOI: 10.1111/1747-0080.12522
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast skipping in Greek schoolchildren connected to an unhealthy lifestyle profile. Results from the National Action for Children's Health program

Abstract: Aim The aim of the present study was to examine prevalence and correlates of skipping breakfast in a representative sample of children and adolescents. Methods Cross‐sectional, observational study. Population data derived from a school‐based health survey carried out in 2015 on 177 091 Greek children aged 8–17 years. Trained investigators performed all anthropometric evaluations. Breakfast skipping and adherence to the Mediterranean diet (MD) was assessed through the Mediterranean Diet Quality Index for childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 34 publications
5
25
1
1
Order By: Relevance
“…In terms of skipping breakfast, findings have been inconsistent, with some studies reporting that it is associated with physical activity [30], while others have reported that they are unrelated [31]. However, in the present study, the rate of achieving the guideline-recommended physical activity level was related to skipping of breakfast in seventh and eighth grade boys of junior high school.…”
Section: Plos Onecontrasting
confidence: 84%
“…In terms of skipping breakfast, findings have been inconsistent, with some studies reporting that it is associated with physical activity [30], while others have reported that they are unrelated [31]. However, in the present study, the rate of achieving the guideline-recommended physical activity level was related to skipping of breakfast in seventh and eighth grade boys of junior high school.…”
Section: Plos Onecontrasting
confidence: 84%
“…Such findings appeared similar to those reported recently for primary school children from Riyadh [27]. The link between higher frequency of breakfast consumption and healthier BMI scores has been established in the literature [2,7,8,16,40]. Our present findings did not observe any association between the type of school and BMI status (e.g., overweight or obesity levels).…”
Section: Discussionsupporting
confidence: 93%
“…Higher levels of essential micronutrients including vitamin D, vitamin C, and folate have also been observed in European adolescents who consumed breakfast compared to those who skipped the breakfast meal [6]. Conversely, breakfast skipping is associated with several negative health effects and worse anthropometrics including higher body mass index (BMI) z-scores, waist circumferences, and overweight/obesity prevalence among children and adolescents [2,7,8]. A systematic review of studies from 33 countries found that skipping breakfast also negatively altered blood lipid profiles and may be associated with an increased risk for developing the metabolic syndrome, a finding possibly explained by higher postprandial glycemic response in breakfast skippers [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five of the six articles reviewed were assessed as high risk of bias, with the assessment tool criteria most frequently unmet relating to exposure measurement and confounder adjustment. The ambiguity and inconsistency of breakfast definitions observed in articles reviewed reflect the state of the broader literature on breakfast consumption, 2,34,35 and as breakfast consumption frequently correlates with established health determinants such as diet quality, residual confounding is likely 4,31,36 . The importance of considering not only whether breakfast is consumed but also what is being consumed at breakfast is recognised in the broader literature 1,2 .…”
Section: Discussionmentioning
confidence: 99%